2016
DOI: 10.1007/s00122-016-2698-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined linkage and association mapping identifies a major QTL (qRtsc8-1), conferring tar spot complex resistance in maize

Abstract: A major QTL ( qRtsc8 - 1 ) conditioning resistance to tar spot complex of maize and occurring at a frequency of 3.5 % across 890 maize inbred lines. Tar spot complex (TSC) is a highly destructive disease of maize found in some countries in America. Identification of TSC resistant germplasm and elucidating the genetic mechanism of resistance is crucial for the use of host resistance to manage this disease. We evaluated 890 elite maize inbred lines in multiple environments and used genome wide association analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 43 publications
4
57
1
4
Order By: Relevance
“…Best linear unbiased prediction (BLUP) value of genotypes, variance components, and broad‐sense heritability were obtained. A previous study (Mahuku et al, 2016) indicated that response to TSC was negatively correlated with maturity. Thus, anthesis date (data not shown) was used as a covariate to correct maturity effect and calculate the final TSC disease response BLUP.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Best linear unbiased prediction (BLUP) value of genotypes, variance components, and broad‐sense heritability were obtained. A previous study (Mahuku et al, 2016) indicated that response to TSC was negatively correlated with maturity. Thus, anthesis date (data not shown) was used as a covariate to correct maturity effect and calculate the final TSC disease response BLUP.…”
Section: Methodsmentioning
confidence: 94%
“…Each plot consisted of a single 2‐m row with 10 plants per row. Disease evaluation was performed as described by Mahuku et al (2016). Briefly, disease scores were first taken at 2 wk after flowering and repeated two times at 7‐d intervals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this strategy allows the identification of many new loci in the complex genetic background of crops (Li et al, 2016a;Motamayor et al, 2013). Hence, it is preferable to perform combined analyses of multiple populations to dissect the genetic basis of a trait (Lee et al, 2014;Mahuku et al, 2016;Motte et al, 2014;Sun et al, 2016;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Illumina GoldenGate has been the most widely used platform for SNP genotyping, while Sequenom MassARRAY platform-based SNP-typing assays are becoming popular as well (Oliver et al, 2011; Chagné et al, 2015). SNP-based high density linkage and transcriptome map construction using NGS data has been successful in wheat (Wu et al, 2015; Holtz et al, 2016), rice (Xie et al, 2010; Zhang et al, 2015), maize (Liu et al, 2010; Mahuku et al, 2016), barley (Chutimanitsakun et al, 2011; Obsa et al, 2016), perennial ryegrass (Pfender et al, 2011; Paina et al, 2016; Velmurugan et al, 2016), orchardgrass (Zhao et al, 2016), intermediate wheatgrass (Kantarski et al, 2017), and zoysia grass ( Zoysia japonica ) (Wang F. et al, 2015). NGS-derived SNP-based genetic maps are useful for comparative mapping and have great potential for cool-season perennial grasses with limited genomic information available.…”
Section: Genomics Tools and Resourcesmentioning
confidence: 99%